Rectal cancer lateral lymph nodes: multicentre study of the impact of obturator and internal iliac nodes on oncological outcomes. Issue 2 (23rd January 2021) - Schaap, D P; Boogerd, L S F; Konishi, T; Cunningham, C; Ogura, A; Garcia-Aguilar, J; Beets, G L; Suzuki, C; Toda, S; Lee, I K; Sammour, T; Uehara, K; et al.
Abstract: Background: In patients with rectal cancer, enlarged lateral lymph nodes (LLNs) result in increased lateral local recurrence (LLR) and lower cancer-specific survival (CSS) rates, which can be improved with (chemo)radiotherapy ((C)RT) and LLN dissection (LLND). This study investigated whether different LLN locations affect oncological outcomes. Methods: Patients with low cT3–4 rectal cancer without synchronous distant metastases were included in this multicentre retrospective cohort study. All MRI was re-evaluated, with special attention to LLN involvement and response. Results: More advanced cT and cN category were associated with the occurrence of enlarged obturator nodes. Multivariable analyses showed that a node in the internal iliac compartment with a short-axis (SA) size of at least 7 mm on baseline MRI and over 4 mm after (C)RT was predictive of LLR, compared with a post-(C)RT SA of 4 mm or less (hazard ratio (HR) 5.74, 95 per cent c.i. 2.98 to 11.05 vs HR 1.40, 0.19 to 10.20; P < 0.001). Obturator LLNs with a SA larger than 6 mm after (C)RT were associated with a higher 5-year distant metastasis rate and lowered CSS in patients who did not undergo LLND. The survival difference was not present after LLND. Multivariable analyses found that only cT category (HR 2.22, 1.07 to 4.64; P = 0.033) and margin involvement (HR 2.95, 1.18 to 7.37; P = 0.021) independently predicted the development of metastatic disease. Conclusion: Internal iliac LLN enlargement is associated with an increased LLR rate, whereas obturator nodes are associated with more advanced disease with increased distant metastasis and reduced CSS rates. LLND improves local control in persistent internal iliac nodes, and might have a role in controlling systemic spread in persistent obturator nodes. Members of the Lateral Node Study Consortium are co-authors of this study and are listed under the heading Collaborators. Abstract : This multicentre retrospective cohort study, including 1216 patients with low cT3–4 rectal cancer, demonstrated that internal iliac lateral lymph node enlargement is associated with an increased rate of lateral local recurrence, whereas obturator nodes are associated with more advanced disease resulting in increased distant metastasis and reduced cancer-specific survival rates. Lateral lymph node dissection improves local control in persistent internal iliac nodes, and might have a role in controlling systemic spread in persistent obturator nodes.